Effect of ZrO2 doping in physical properties of barium iron niobate ceramics - U. Intatha (2018)
In this work, preparation conditions and effect of ZrO2 doped BaFe0.5Nb0.5O3 ceramics were studied. Relationship between structure and dielectric properties was investigated. Single-phase cubic BFN powder was synthesized by solid-state reaction at 1200°C for 4 hours with heating and cooling rate of 5°C/min. Various amount of ZrO2 doped from 0.1 to 0.5 %weight were used for doping. After that BFN ceramics were formed via uniaxial pressing and sintered at 1300°C for 4 hours with heating and cooling rate of 5°C/min. Physical properties, microstructure, phase evolution and dielectric properties were studied to find out the optimum conditions for high voltage capacitor applications. © 2008 Trans Tech Publications, Switzerland.